The Psychometric Properties of the French–Canadian Stress and Anxiety to Viral Epidemics-6 Scale for Measuring the Viral Anxiety of the General Population During the COVID-19 Pandemic - Park, C. Hyung Keun; Ahmed, Oli; Lee, Sangha; Suh, Sooyeon; Chung, Seockhoon; Gouin, Jean-Philippe (Frontiers in Psychiatry, 2022)
Objective: This study examined the psychometric properties of the Canadian French version of the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale for assessing the anxiety response of the French-speaking general population in Quebec, Canada, to the viral epidemic. Methods: A total of 590 participants responded to the anonymous online survey between September 28 and October 18, 2020. Confirmatory Factor Analysis (CFA) was conducted to explore the factor structure of the scale. Psychometric properties were assessed using the Item Response Theory (IRT) approach. To explore the convergent validity, a Pearson correlation analysis between the SAVE-6 scale and the depression (Patient Health Questionnaire-2, PHQ-2) or anxiety subscale (Generalized Anxiety Disorder-2, GAD-2) of the Patient Health Questionnaire-4 items scale was conducted. Findings: The Canadian French version of the SAVE-6 scale was clustered into a single factor. The CFA of the SAVE-6 scale showed a good model fit (CFI = 0.985, TLI = 0.976, RMSEA = 0.051, RSMR = 0.048), and the multi-group CFA revealed that the SAVE-6 scale can measure anxiety response in the same way across gender or the existence of depression or anxiety. It showed good internal consistency (Cronbach’s alpha = 0.76, McDonald’s Omega = 0.77) and significant correlation with the PHQ-2 score and GAD-2 score. The IRT model suggested the efficiency in discrimination among individuals in this latent trait. Conclusion: The Canadian French version of the SAVE-6 scale is a valid and reliable rating scale, which can measure the general population’s anxiety response to the viral epidemic.